Drinking Habits of School Youth (Based on a Study Conducted in the School of Bochnia in the Years 1913, 1967, and 1990) (Archives of Criminology, 1994)
The paper discusses the findings of a studv into the structure of consumption of alcoholic beverages by school youth in Bochnia. The findings reflect the situation in that sphere in 1990 as compared to 1913 and 1967. The choice of Bochnia as the area to be examined, and also of the years 1913 and 1967 as the basis for comparisons, was not accidental. Available are the findings of a study of consumption of alcoholic beverages by school youth of that town conducted in 1913 by a district school superintendent J. Ciembroniewicz, and also of a 1967 study conducted by J. Bardach from the Research Center of the Main Board, Social Anti-Alcoholic Committee headed by A. Święcicki.Most of the Bochnia school youth examined in 1990 have the same regional background as the persons examined in 1913 by J. Ciembroniewicz and in 1967 by J. Bardach. Since 1913, and then since 1967, certain cultural and moral transfomations have taken place; yet the changes do not seem to be tooo extensive, the mores so as there was no increase in migration of the population in the discussed area. A possible explanation of this rather low mobility is that, during the decades  covered by this paper, no large undustrial plants were built in Bochnia which would attract people from various regions of Poland, with their different cultural and moral patterns, acting towards transformation of the town’s original social structures. On the other hand, the local industrial plants, the Metallurgical Processing Factory and the Salt Mine in particular, as well as trade and services were developed enough to offer a sufficient numer of workplaces to the  population of Bochnia.In 1913, J. Ciembroniewicz examined 2098 young persons not older than 14. His report makes no mention of the numer of schools included in the  survey, stating only that youth from all types of schools were examined. 1231 boys and 867 girls were the respondents of a questionnaire survey. The extend to which this sample was representative cannot be appraised today for lack of detailed data as to the total school population in Bochnia in 1913. The material gathered by J. Ciembroniewicz should be seen as sufficiently extensive to evaluate the structure of  consumption of alcoholic beverages by the Bochnia school youth of those days.The 1967 study was a questionnaire survey of a sample of children from forms 5 – 8 of all Bochnia elementary schools, aged 14 at the most. The sample  consisted of 1314 persons; 1199 quetionnaires were submitted to analysis. Examined in 1990 were all children of forms 5 – 8 of Bochnia elementary schools present at school on the day of the survey (absent were e.g. the sick children). The sample consisted of 1500 persons, and 1437 questionnaires were analysed (the remaining 63 were rejected for various defects).The basic purpose of the study was: (1) to define the changes in drinking habits and the structure of consumption of alcoholic beverages during the 20th century, and (2) to show the socio-educational effects of the parents’ drinking on the shaping of their children’s attitudes towards alcohol.In all three studies, a questionnaire was used to gather data. The 1990 questionnaire was designed so as to include questions the same as or similar to those asked on 19l3 and 1967. The questionnaire used by J. Bardach, however, was not a verbatim repetition of that prepared by J. Ciembroniewicz. New questions were added, and some of those original were reformulated for precision or written in the modern language. The 1990 author took similar steps. The questionnaires were distributed to the children who wrote their answers by themselves.The findings were as follows:           (1) In 1990 as compared to l967, and in 1967 as compared to 19l3, the proportion of school youth who drank alkoholic beverages went down in Bochnia. This is true for boys and girls alike. In 1913, the proportion of girls who drank nearly equalled that of boys but proved much lower both in 1967 and in 1990.            (2) Considerable changes also took place in consumption of the separate alcoholic beverages. In 1990 as compared to 1967, and in 1967 as compared to 1913, consumption of both beer, wine, vodka was the decrease. The only exception here is a slight growth in the consumption of beer in 1967 as compared to 1913. Generally speaking, however, the proportion of beer drinkers was 2 times lower, and that of vodka drinkers – over 3.5 times lower. This drop between the years 1913 and 1990 was particularly marked in the case of girls: consumption of beer was over 4 times lower, of wine – over 2 times lower, and of vodka – nearly 6 times lower in 1990 as compared to 1913.            (3) Also the frequency of consumption of alcoholic beverages by the youth went down. The later the study, the smaller the proportion of both boys and girls who drank alcohol often and very often. The above concerns respondents of all age groups.(4) In general, the highest proportion of boys always drank in the company of their parents. The exception here is the 1967 sample: the boys then drank most often with their peers. In 1913, 1967, and 1990 alike, the proportion of boys who drank in the company of their parents went down with age. A similar trend was found in the case of boys who drank in the company of other adult family members. What grew with age, instead, was the proportion of boys who drank in the company of their peers, on their own, or together with adults from outside their family.As regards girls, in 1913, 1967, and 1990 alike, most of those who at all drank alcoholic beverages did it in the company of their parents.Striking among both boys and girls is the high proportion of young personswho drank in the company of their peers or on their own. This trend was particularly marked in l967 as compared to 1913. This finding is  the more important as in the case of this group, the role of the family as controller of the alcohol-related habits and particularly the type and amount of alcohol consumed was largely reduced.            (5) In l9l3, 1967, and 1990 alike, most boys drank on church holidays, at festivities, weddings, celebrations of baptism, and parties, that is occasionally.(6) As for the yoith’s contacts with drinking persons, the situation proved much different in 1990 as compared to 1967 and 1913. In 1967 and 1990, 2 times as many boys as in 1913 saw a drink parent or older sibling. In the case of girls, this difference between l9l3, 1967, and1990 is greater still.*      *     *The findings of the 1990 study manifest the occurrence over the years of advantageous changes in the drinking habits and structure of consumption of alcoholic beverages among children up to 14 in small towns.  Interestingly enough, there is a continuous discrepancy between two groups of data: in the period 1913‒1990, there was a regular  decrease in the proportion of young persons who had drank alcohol at least once before the survey while the general extent of alcohol consumption was on a constant increase. These data correspond with national findings which show that today, about 50–60 % of young persons in the discussed age group drink alcohol.In the age15 to 18, as many as over 80% of Polish youth accasionally drink alcohol.The general social knowledge on the harmful effects of drinking is much more extensive today than it was in the early 1900’s. At present, hardly  any mothers use an  alcohol-soaked cloth to calm their babies; hardly any parents treat their thirsty children to a beer during harvest; hardly any fathers have a drink with  their small sons. Such practices did take place earlier in our century.Even if they drink themselves, the parents and educators of today are aware of the threats involved in drinking and try hard to delay the children’s first encounter with alcohol. With the child’s growing criticism, the discrepancy between the adults’ opinions and their actual drinking habits noticed by juveniles makes the latter reach for alcohol. Another factor that greatly contributes here is the reduced authority of the family and the growth of importance of a peer group. All these processes are not intensified until puberty, that is after the age of 14.This is not to say, however, that alcohol consumption at its present level is low. After all, the 50 to 60% of  children aged up 14 who at least occasionally drink alcohol constitute a very high proportion.